Do the blood pressure changes in association with continuous positive airway pressure compliance play an important role to improve cardiovascular outcomes? - Murata, Azusa; Kasai, Takatoshi (Journal of Thoracic Disease, 2017)
Obstructive sleep apnea (OSA) is a common chronic condition, observed in 5–10% of the general population, though it is more prevalent in patients with cardiovascular disease (CVD) (up to 50%) (1). The high prevalence of OSA in patients with CVD raises several questions, such as, can OSA [which is known to have adverse cardiovascular (CV) effects (2)] contribute to the incidence and/or development of CVD? In other words, are there any causal relationships between OSA and poor CV outcomes?